High yield Q & A review for USMLE step 1 : biochemistry and genetics - King, Michael W. (Michael William) (New York : McGraw Hill Education, 2023)
"Primarily Q/A-this text offers a and effective way for students to prepare for regular course examinations and preparing for the USMLE Step 1 in biochemistry. Packed with valuable learning aids: 1,100 multiple-choice questions Thorough explanations for each answer Checklists that recap important and high-yield concepts Detailed clinical boxes presenting high-yield information concerning diseases and disorders related to defects in the pathways"--
Includes bibliographical references and index
Keywords: Biochemistry.D001671https://id.nlm.nih.gov/mesh/D001671; Examination Questions.D020475https://id.nlm.nih.gov/mesh/D020475